(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The purpose of this article was to identify the conceptions of the history of science held by teachers in initial training. A qualitative-descriptive methodology was used. The data were obtained from an initial questionnaire, structured by open-ended questions and the construction of a final written document applied to twenty-five participants on a degree program at Universidad del Valle. The results of the proposal were obtained from a descriptive analysis of three categories (vision of the history of the sciences, function of the history of the sciences in teaching and production of science) which made it possible to determine that the conceptions of the history of the sciences that teachers in initial training have elaborated correspond to anachronistic and diachronic visions, functions such as social activity, resource and disciplinary, and production of knowledge. As a conclusion, we can establish that it is necessary to implement didactic proposals directed toward the use of the history of science so as to promote in teachers the recognition, reflection, and use of historical components in their educational practices.